Adaptation in action: The transition from research to intervention - Schinke, R. J.; Tenenbaum, G.; Lidor, R.; Battochio, R. C. (The Sport Psychologist, 2010)
Adaptation is defined here as the end point in a process, when people respond in a positive manner to hardship, threat, and challenge, including monumental sport tests, such as international tournaments. Recently, there have been formal research investigations where adaptation has been considered as a provisional framework, with a more formal structure of pathways. Sport scholars have studied Olympic and professional athletes, provided support for a theoretical framework, and identified provisional substrategies for each pathway. In this article the authors situate adaptation within a larger discourse of related interventions, including coping and self-regulation. Subsequently, adaptation is proposed as a comprehensive intervention strategy for elite athletes during monumental sport environments.